Feasibility of introducing takaful (Islamic Insurance) in India from the perspective of islamic finance experts - Salman S.A.; Hassan R.; Yusoff A. (Institute of Medico-Legal Publications, 2023)
adult; article; e-mail; feasibility study; finance; human; human tissue; India; insurance; interview; male; perception; sampling